(untitled) (Al-Academy, 2024)
Artificial intelligence has entered many aspects of our lives, and design is by no means an exception. In the past two years, we have witnessed rapid development in this sector. Many new solutions have emerged, flooding the software market and providing opportunities for designers to change the way they create and collaborate. In this article we provide an overview of the current use of AI in graphic design and discuss the role it may play in the design process. The primary goal of AI tools in graphic design has been optimization and speed – replacing designers in doing repetitive tasks or analyzing massive amounts of user data to create better solutions. Today, AI not only speeds up processes, allowing designers to focus on the creative part of their work, but also creates designs from scratch by following user inputs. Today, AI has been integrated into a variety of economies, and the design industry is no exception: AI is increasingly being applied in the development of design products and services. However, as technological breakthroughs rapidly shift the boundaries between work tasks performed by humans and those performed by machines and algorithms, global labor markets are undergoing major transformations. This raises the question: How are these changes impacting and will continue to impact the work of designers in the future? What skill sets are needed for designers to start or continue working in this industry? The article aims to conduct a meta-analysis, summarizing research on the impact of artificial intelligence on the professional activity of the designer and testing the capabilities and results of design solutions based on artificial intelligence. Research methods - theory - research and analysis of literature and Internet resources; Experimental – a case study to analyze the possibilities and outcomes of AI-based design solutions